(untitled) (New York, N.Y., 2008)
Growing Up! A Parents' Guide to Childhood is a comprehensive companion for parents. Written by a panel of top parenting and medical experts, the book covers the physical, emotional, and cognitive aspects of your children's development, from ages 3-14. It will guide parents through every aspect of their child's development-from building a little one's confidence as a toddler to teaching an adolescent about responsibility. Clear facts, such as on growth stages, physiological changes, and health issues lie side-by-side with easy to follow advice and practical parenting tips. Parents can refer to the book each year to see what major issues may lie ahead, and they can dip into it whenever they need advice or hit a new milestone.
Keywords: Child rearing,Parenting